Hungarian Monitoring, 21 September 1989 . [Magyar rádiófigyelő], 1989. szeptember 21 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Baker and Shevardnadze in talks - USSR: Sino-Soviet talks on reducing border troops, cadre changes within the USSR - GDR Interior Ministry bans "New Forum" alternative group Domestic Affairs: - Ministerial council in session: modifying the constitution, how parties operate, constitutional court and election of representatives - Meeting between Austrian socialist and Hungarian social democrats - Alliance of Young Democrats (Fidesz) mediates call for resignation of 4 Debrecen representatives - Iran calls off visit of two Hungarian ministers - Archbishop of Esztergom Paskai in the US Economy: - Sándor Nagy recommends that the government request 1-2 years' suspension of its debt repayment obligations - Economist László Lengyel on the economic problems of the 1990s: debt, relations with Comecon, stabilization Külpolitika: - Baker és Sevardnadze tárgyalásai - SZU: szovjet-kínai tárgyalások a határ menti csapatok csökkentéséről, SZKP-beli kádercserék - Az NDK belügyminisztériuma betiltotta az Új Fórum nevű alternatív csoportot Belpolitika: - A Minisztertanács ülése: az alkotmány módosításáról, a pártok működéséről, az alkotmánybíróságról és a képviselőválasztásról - Osztrák szocialisták és magyar szociáldemokraták találkozója - A FIDESZ közvetítésével lemondásra szólítottak fel négy debreceni képviselőt - Irán lemondta két magyar miniszter látogatását - Paskai esztergomi érsek az Egyesült Államokban Gazdaság: - Nagy Sándor javasolja, hogy a kormány kérje adósságfizetési kötelezettségének egy-két éves felfüggesztését - Lengyel László közgazdász a kilencvenes évek gazdasági problémáiról beszél: adósságteher, KGST-kapcsolat, stabilizáció